The Formation of Ultra-Micro Holding of BRI, Pawnshop, and PNM on Profitability and Capital Ratios in BRI - Abror, Ghozi; Muharam, Harjum (Devotion : Journal of Research and Community Service, 2024)
To encourage national development with the Government encouraging the revival of the Medium, Small and Micro Enterprises (MSMEs) and Ultra Micro (Umi) sectors, through the Ministry of SOEs. The presence of the UMi program through ultra-micro holding is expected to develop micro businesses, reduce poverty levels, improve community welfare, and contribute to national economic growth. The purpose of this study was to determine the impact of holding ultra micro BRI, pawnshop, and PNM on increasing BRI's profit in the micro segment. The research method used is literature review with a qualitative approach. The data source used is secondary data. The data collection technique is done by means of documentation, namely data collection techniques through written materials published by the institution that is the object of research. The analysis technique is by data reduction, data presentation, and conclusion drawing. The results showed that the existence of ultra-micro holding had a real impact on increasing BRI's profit in the micro segment, showing the success of the integration strategy in supporting the growth and sustainability of BRI's business in the MSME sector.